THE DEVELOPMENT OF NURSING CARE MODEL IN PATIENTS WITH TOTAL KNEE REPLACEMENT RECONSTRUCTIVE SURGERY: Received: 27th January 2023, Revised: 19th March 2023, 16th April 2023, Accepted: 21st April 2023 - Santisathaporn, Rattiya; Chokpiriyawat, Thanuset (LIFE: International Journal of Health and Life-Sciences, 2023)
This research aims to develop a nursing care model for patients undergoing total knee replacement surgery (TKR) using the models Kemmis and McTaggart (1988) as development guidelines. The study has started from April to July 2020 in Operation Department, Loei hospital, Thailand. The purposive sampling method has been selected with participant nurses (n=50). The mixed method design has been used to obtain the new development nursing care model and guidelines for patient care, proper assignment system, and follow-up techniques. The result showed the nurse behavior changed before to after implementing a model in pre-operation, intra-operating, and post-operation stages statistically different at p less than .001 (mean = 4.9 ± 0.1, p<0.001, mean = 1.9 ± 0.1, p<0.001, mean = 2.0 ± 0.0, p<0.001) respectively. The nurse’s satisfaction level after cycle 2 was significantly higher than cycle 1 (mean = 4.2 ± 0.3, p<0.001). The development of the new nursing care model in TKR surgery could lead to changes in the system with gained positive feedback from OR nurses. The nursing leadership, group motivation, and a cooperative nursing team contributed to the successful operation of the new model. This research recommended following this model’s protocols as a routine and further expanding to other departments such as outpatient, inpatient, and continuous care units.